Factors Influencing Whistleblowing intention among administrative and Diplomatic Officers at Malaysian selected public organizations - Abdul Aziz, Putri Sherina Aizat; Alias, Siti Noormi (Human Resource Management Academic Research Society, 2023)
Although there are various policies introduced to prevent civil servants from getting involved, the problem of misconduct is still happening. Therefore, certain practice recommendations are needed to help overcome the problem of wrongdoing. Therefore, this study has been conducted to determine the influence of personal responsibility, fraud seriousness, and organizational commitment to whistleblowing intention among Administrative and Diplomatic Officers (ADOs) in Putrajaya based on Ethical Climate Theory. This study was accomplished through descriptive and correlational research design, which involved 131 ADOs working in Putrajaya. The constructs of this study have been adapted from past studies and their validity and reliability confirmed throughout the study. Personal responsibility, fraud seriousness, and organizational commitment to whistleblowing intention are significantly correlated. Meanwhile, with a variance of 40.3%, fraud seriousness is the most dominant predictor of whistleblowing intention among ADOs in Putrajaya. This study provides significant insights into the field of study as well as to ECT.